The OCD Workbook for Kids : Help for Kids with Obsessive Compulsive Disorder. - Puliafico, Anthony C. (New Harbinger Publications, 2017)
Children with obsessive-compulsive disorder (OCD) may suffer from obsessive thinking, use rituals to soothe their anxiety, and act compulsively in ways that are disruptive and sometimes harmful. As parents know all too well, OCD can greatly interfere with school, friends, and home life. In this important and much-needed Instant Help workbook, kids will learn to identify obsessions and compulsions, understand them, and use simple tools based in exposure and response prevention to cope with and overcome OCD.